Implementasi Vending Machine Ramen dengan Menggunakan Mealy Machine - Ammara Desma Marzooqa; Farhatush Shalihah Yumna; Finna Luthfiah Hafizh; Tedy Setiadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Ramen is a Japanese specialty that is widely favored by Indonesians. One implementation of innovation to significantly increase ramen sales is with vending machines. In Indonesia, vending machines are not yet widely known, especially in the food category. To take advantage of this business opportunity, vending machines are one of the solutions. Vending machine is a strand of technology whose concept is to make manual activities automatic with the aim of running production and making the output more quality. With this, the purpose of this research is to implement the concept of automata language theory with the Mealy Machine model. This research uses analytical methods, namely from the information obtained and formal methods to analyze how the vending machine works starting from business process analysis, FSA diagram design, FSA testing, and UI Concept Design based on FSA on vending machines. The results of this study are in the form of test results using JFLAP software that can help analyze the patterns that have been made and can be simulated to ensure compliance with the planned design.